Poor agreement between indirect calorimetry and predictive formula of rest energy expenditure in pre-dialytic and dialytic chronic kidney disease - de Oliveira, Mariana Cassani [UNESP]; Bufarah, Marina Nogueira Berbel [UNESP]; Ponce, Daniela [UNESP]; Balbi, André Luís [UNESP] (Elsevier, 2018)
Background/aims: Protein-energy wasting (PEW) is common in the end-stage of chronic kidney disease (CKD) and can be caused by factors related to poor dietary intake and changes in energy expenditure. Indirect calorimetry (IC) is the gold standard method to measure resting energy expenditure (REE), however, it is not much available and it is common to use predictive formulas of REE in clinical practice. This study compared the values of REE measured by IC to those estimated by Harris & Benedict formula, the most one used in clinical practice in Brazil. Methods: Patients with stage 5 CKD (an estimated glomerular filtration rate <15 mL/min/1.73 m2), >18 years old were included and submitted to the IC test and Harris & Benedict's predictive formula. The assessments were performed at three moments: pre-dialysis indications (P1), at the beginning of dialysis indication (P2) and 30 days after the start of dialysis therapy (P3). Tuckey's test was used to compare energy expenditure variable by groups, and the Bland & Altman analysis was used to compare the agreement between the methods. A significance level of p < 0.05 and agreement limits of up to 200 Kcal were used. Results: Thirty-five patients with mean age of 61.2 ± 10.9 years were included, 60% female, 17% afrodescendants and 60% with diabetes mellitus. There were no significant differences in REE between the three moments (P1: 1289.8 ± 382.7 kcal, P2: 1218.2 ± 362.8 kcal, P3: 1269.5 ± 335.1 kcal, p = 0.874). Harris & Benedict formula did not show IC agreement for the REE measurement because it presented high limits of agreement or because of the low precision of the estimated measure. Conclusion: This study showed that there was no significant alteration of REE by IC and that REE values estimated by Harris & Benedict formula did not agree with the values measured by IC in this population. The role of Harris & Benedict formula should be re-evaluated in stage 5 CKD patients.
Keywords: Chronic kidney disease; Indirect calorimetry; Resting energy expenditure